Pemanfaatan Abu Sekam Padi dalam Meningkatkan Serapan P pada Produksi Tanaman Kedelai (Glycine max L.) - lufita nur alfiah (PUCUK : Jurnal Ilmu Tanaman, 2025)
Soybean production in Riau Province has decreased one of the factors that affect the growth and production of soybean plants is nutrients, where phosphorus plays a very important role. Nutrient P is an important element after nitrogen which plays a role in photosynthesis, respiration, cell division and enlargement, root development, formation of flowers, fruits and seeds This study aims to determine the effect of rice husk ash in increasing P uptake on soybean crop production. The study was carried out with a Complete Random Design (RAL) consisting of four husk ash treatments with doses (0, 20, 30, and 40, grams/polybag) with three replicates, so that 12 experimental units consisting of 6 plants were obtained, of which there were 3 samples. The observed variables included analysis of P content in soil and husk ash, flowering age, harvest age, number of pods and weight of 100 seeds. The results showed that the application of husk ash had a real effect on the harvest age and the number of pods/sample plants at a concentration of 40 grams/polybag, but had no real effect on the flowering age and weight of 100 seeds.